Consciousness-specific dynamic interactions of brain integration and functional diversity - Andrea I. Luppi (Nature Portfolio, 2019)
How do diversity (entropy) and integration of activity across brain regions interact to support consciousness? Here the authors show that anaesthetised individuals and patients with disorders of consciousness exhibit overlapping reductions in both diversity and integration in the brain’s default mode network.